Innovation in Antenna Testing: Development of an Automatic Measurement System for Gain and Radiation Pattern of a 4×1 Microstrip Array Antenna - Junfithrana, Anggy Pradiftha (Universitas Pendidikan Ganesha, 2025)
The need for a more automated, precise, and integrated antenna measurement system has become urgent. The main objective of this research is to develop and test an automatic antenna measurement system based on LabVIEW that can improve the accuracy and efficiency of measuring the gain and radiation pattern of a 4x1 microstrip antenna. This research is a study of the development and validation of an experimental system using a 4×1 microstrip antenna array as the research subject, with an automatic measurement system based on an Arduino microcontroller (AT-Mega328) and stepper motor, as well as LabVIEW software for instrument control, data acquisition, real-time transmission, and user interface. Data collection was performed automatically via a roll-over-azimuth rotator. In data analysis, the results of the automatic system were quantitatively compared with CST simulation results and a semi-automatic system using 2D correlation coefficients and gain differences. At the same time, the benefits of improved time efficiency were also measured. The findings of this research indicate that the developed automatic measurement system provides a practical, efficient, and cost-effective solution for educational laboratories and industrial antenna testing, with potential for further development to support higher frequency ranges and three-dimensional measurements. The findings of this study have implications for improving the efficiency, accuracy, and flexibility of microstrip antenna testing and for offering practical and economical solutions for laboratory and industrial needs.